Cost-effectiveness of prevention and early detection of gastric cancer in Western countries - Lansdorp-Vogelaar, Iris; Meester, Reinier G.S.; Laszkowska, Monika; Escudero, Fernando Alarid; Ward, Zachary J.; Yeh, Jennifer M. (Baillière's best practice & research. Clinical gastroenterology, 2021)
Gastric cancer (GC) is a significant global health problem, with Helicobacter pylori infection estimated to be responsible for 89% of non-cardiac GC cases, or 78% of all GC cases. The International Agency for Research on Cancer has called for Helicobacter pylori test-and-treat strategies in countries with high rates of GC. However, for countries with low rates of GC, such as most Western countries, the balance between benefits, harms and costs of screening is less clear-cut. GC is a disease with a well-characterized precancerous process, providing the basis for primary and secondary prevention efforts. However, rigorous data assessing the impact of such interventions in Western countries are lacking. In the absence of clinical trials, modelling offers a unique approach to evaluate the potential impact of various screening and surveillance interventions. In this paper, we provide an overview of modelling studies evaluating the cost-effectiveness of GC screening and surveillance in Western countries.